2007
DOI: 10.1016/j.neuroscience.2006.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of cannabinoid receptor type 1 expression in rodent somatosensory cortex

Abstract: Endocannabinoids are powerful modulators of synaptic transmission that act on presynaptic cannabinoid receptors. Cannabinoid receptor type 1 (CB1) is the dominant receptor in the CNS, and is present in many brain regions, including sensory cortex. To investigate the potential role of CB1 receptors in cortical development, we examined the developmental expression of CB1 in rodent primary somatosensory (barrel) cortex, using immunohistochemistry with a CB1-specific antibody. We found that before postnatal day (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 52 publications
6
29
0
1
Order By: Relevance
“…Coincident adolescent development of the cortical eCB system includes reduced CB1R expression (Deshmukh et al, 2007;Heng et al, 2011) and changes in eCB metabolism (Long et al, 2012). The highly dynamic nature of glutamatergic, GABAergic, and eCB system development parallels the maturation of cortical oscillations that are suppressed by cannabinoids, and may underlie the attenuation of cortical oscillations that we observe after adolescent cannabinoid exposure.…”
Section: Discussionmentioning
confidence: 67%
“…Coincident adolescent development of the cortical eCB system includes reduced CB1R expression (Deshmukh et al, 2007;Heng et al, 2011) and changes in eCB metabolism (Long et al, 2012). The highly dynamic nature of glutamatergic, GABAergic, and eCB system development parallels the maturation of cortical oscillations that are suppressed by cannabinoids, and may underlie the attenuation of cortical oscillations that we observe after adolescent cannabinoid exposure.…”
Section: Discussionmentioning
confidence: 67%
“…S1). Low expression was observed in layer 4 of the somatosensory cortex (9), corresponding to the whisker barrels (Fig. 1C).…”
Section: Resultsmentioning
confidence: 97%
“…For example, it was reported that the level of mRNA expression of CB 1 R in the rat cerebral cortex measured by in situ hybridization was high at P1 and P5 and became very low in the adult, although the specific CB 1 R binding assessed by radioautography in the adult was higher than that at P1 and P5 (Berrendero et al, 1999). By immunohistochemistry, however, it was reported that CB 1 R immunoreactivity appeared in layer II/III of the rat somatosensory cortex around P6, becoming very intense by P12-P16, and then remained high in the adult (Deshmukh et al, 2007). Thus, the developmental changes in the expression level of CB 1 Rs assessed by different methods in the cerebral cortex seemed not completely consistent with each other, and the disappearance of hetero-LTD in the adult might not be explained solely by the developmental changes in CB 1 Rs in the visual cortex.…”
Section: Developmental Changes In Hetero-ltdmentioning
confidence: 93%